PENDIDIKAN KARAKTER BERBASIS BUDAYA DAN LINGKUNAN SEKOLAH - Ahmad Nurabadi (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2019)
Abstract: This study aims to describe: 1) values of culture-based character education and school environment; 2) implementation of values of culture-based character education and school environment; 3) evaluation of cultural and school-based character education; and 4) supporting and inhibiting factors for cultural and school-based character education. This study uses a qualitative approach with a type of case study research. The results of the study show that: (1) Cultural values consist of discipline and cleanliness by forming Discipline Scrubbing Students (SPD); (2) the programme of seeding students’ character values is carried out with daily habits, planning character values has been designed since the formulation of school activities and plans at the beginning of the year, organizing is implemented on the program and the person in charge of each activity, (3) evaluation Activities are carried out in two activities, namely the evaluation of the activities and results of activities, reported to the principal in a verbal and written manner. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan: 1) nilai-nilai pendidikan karakter berbasis budaya dan lingkungan sekolah; 2) implementasi nilai-nilai pendidikan karakter berbasis budaya dan lingkungan sekolah; 3) evaluasi pendidikan karakter berbasis budaya dan lingkungan sekolah; dan 4) faktor pendukung dan penghambat pendidikan karakter berbasis budaya dan lingkungan sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Hasil penelitian menunjukkan bahwa: (1) Nilai-nilai budaya terdiri dari kedisiplinan dan kebersihan dengan membentuk Siswa Pengerak Disiplin (SPD); (2) program penyemaian nilai-nilai karakter siswa dilakukan dengan pembiasaan sehari-hari, perencanaan nilai-nilai karakter telah dirancang sejak perumusan kegiatan dan rencana sekolah di awal tahun, pengorganisasian diimplementasikan atas program dan penanggung jawab masing-masing kegiatan, (3) evaluasi kegiatan dilakukan dalam dua kegiatan yaitu evaluasi proses kegiatan dan hasil kegiatan, dilaporkan kepada kepala sekolah secara lisan dan tertulis.